Channel Coordination with a Risk‐Neutral Supplier and a Downside‐Risk‐Averse Retailer - Gan, Xianghua; Sethi, Suresh; Yan, Houmin (Production and Operations Management, 2005)
We investigate how a supply chain involving a risk‐neutral supplier and a downside‐risk‐averse retailer can be coordinated with a supply contract. We show that the standard buy‐back or revenue‐sharing contracts may not coordinate such a channel. Using a definition of coordination of supply chains proposed earlier by the authors, we design a risk‐sharing contract that offers the desired downside protection to the retailer, provides respective reservation profits to the agents, and accomplishes channel coordination.